Theory of judgment in the Lvov School of Philosophy: introduction to research - Ivanyk, Stepan (Lviv Politechnic Publіshing House, 2015)
Current knowledge of philosophical and logical investigations includes numerous gaps regarding the theory of judgment in the Lvov School of Philosophy. The aim of the paper is to show that the task of filling this gap is not without merit and to outline the way how to complete this task. Theoretical and methodological roots of theory of judgement of the Lvov School in philosophy lies in philosophy of Franz Brentano, whose views on logic have been identified as the first ever revolt against Aristotelian logic. This fact increases the theoretical and practical value of attainments in the theory of judgement of the School as one of the most potent centers of Brentano’s philosophy, and justifies the necessity to scrutinize and systematize them. In turn, taking into consideration the fact that for specific interpretations of judgement in the School there were mainly innovative constructions of logic, conducting such a study seems to be crucial not only from the historical point of view (as the reconstruction of an important period of history of Polish philosophy and logic in Lvov) but also can provide plenty of interesting issues and serve as the source of inspiration for contemporary logic and meta-logic research. Therefore the way how to complete the task of the paper is like following: (1) to reconstruct a full range of theoretical propositions in the theory of judgment devised in the Lvov School; (2) to explicate epistemic and ontic foundations of theoretical propositions of the School and (3) to find, analytically develop, and introduce to science so far unknown scientific materials (dissertations, readings and academic lectures, correspondences, etc.). Сучасний стан досліджень наукової спадщини львіської філософської школи має численні прогалини, однією з яких є теорія судження цієї школи. Показано важливість завдання заповнення цієї прогалини і окреслено шлях виконання цього завдання.
Теорія судження у Львівській філософській школі: вступ до дослідження
Keywords: The Lvov School of Philosophy; theory of judgment; research; львівська філософська школа; львівська філософська школа; дослідження